Administrasi Keuangan bagi Karang Taruna Mahkota Desa Bandungrejo Kecamatan Mranggen Kabupaten Demak - Sudarman Sudarman; Yetti Iswahyuni; Nanik Qosidah; Aniqotunnafiah Aniqotunnafiah (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2019)
Youth organizations have the potential to build the nation and as agents of change, therefore their existence needs to be managed professionally so that they truly contribute to regional development. Within the village environment, there are many potentials that can be developed as alternative capital for regional development. It is hoped that the implementation of strategic management in its management will produce work programs that are appropriate to the needs and potential resources owned by the village/kelurahan, as capital in developing the village. The concept of strategic management includes how an organization makes strategic plans, coordinates and implements programs and evaluates them. In several kelurahans within the sub-district, the existence of youth organizations tended to show less of their role in promoting village development. The existence of this organization seems to be just a formality to complement activities in the village. The awareness of residents to use this organization as a forum for activities and to participate in developing their area is very lacking. The organizing process requires funds to run the programs that have been planned. In general, the obstacles to realizing work programs include funding issues. With sufficient funding, young people can develop their potential, to empower villages and their communities (carry out the activities needed) and provide added value and increase welfare. However, in reality in society, these organizations are not managed properly and optimally because they are constrained by financing. One of the efforts to attract funds is by submitting proposals for funds to certain institutions, both government and non-government organizations. Most of them do not know how to make a proposal for funding an activity. Furthermore, the regional autonomy policy provides opportunities for regions to develop themselves and their communities in accordance with regional needs/interests, so the role of youth as a nation's potential and development constellation cannot be separated from village/sub-district development.